Perilaku Petani dalam Penggunaan Mesin Combine Harvester di Kecamatan Anjir Pasar Kabupaten Barito Kuala - Silaturahmi, Nurul; Hermawan, Hermawan; Ferdinan, Acep (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2022)
The utilization of Combine Harvester Machine technology has become one of the technologies that are currently in demand by farmers in Indonesia, including those in Anjir Seberang Pasar II Village, Anjir Pasar District, Barito Kuala Regency. The acceptance of this technology by farmers varies, thus it is necessary to understand their behavior towards this technology. Therefore, it is expected that farmers can make informed decisions in implementing this technology. This study used a survey method, in which the research area was intentionally selected purposively in Anjir Seberang Pasar II Village, Anjir Pasar District, Barito Kuala Regency, which is the author's extension area. Samples were taken using purposive sampling method, in which 9 farmer groups were chosen, namely Karya Membangun, Tani Sepakat, and Ruhui Rahayu, and then a sample of 30 people was taken disproportion from these 3 farmer groups. Based on the survey conducted, the results showed that the assessment of the farmers' knowledge components towards the use of the Combine Harvester Machine showed a high result of 53,3 percent, while the remaining 46.7 percent were in the low category. And the respondent farmers had a relatively high acceptance attitude with a percentage of 53.3 percent, a moderate attitude of about 16.7 percent, and the remaining 30 percent had a low acceptance attitude.